Issue on Educational Research Innovation - Mila Hasanah (Budapest International Research and Critics University, 2022)
The purpose of this study is to describe the issue of educational research innovation. This research uses a descriptive qualitative method with a literature study. The results of this study are that there are several problems or problems in educational research innovation, including 1) Lack of a strong innovative research culture and community; 2) Lack of innovative research designs; 3) Lack of innovative research talent among education practitioners; 4) Lack of research funds; 5) Excessive reliance on web-based and online information; 6) Lack of motivation; 7) Experienced and qualified research guides are not available. The conclusion of this study as a whole, it is not surprising that research on innovation becomes important. It is important to understand why and how certain enabling environments encourage innovation and help optimize benefits. Among other things, research can explain how innovative action can be applied and how diversity can drive positive change.